Post-harvest storage of lime fruits (Citrus aurantifolia) following high humidity and low temperature in a modified brick wall cooler - Marikar, Faiz Mohideen Mohamed Thassim; Wilson Wijerathnam, R S (International Journal of Agricultural and Biological Engineering, 2010)
The use of a modified brick wall Evaporative Cooling Chamber (ECC) for extending the shelf life of limes (Citrus aurantifolia) was compared with ambient storage. The shelf life inside of the ECC was extended by five to twenty days relative to ambient storage. The inside temperatures were about 4-6